The Role of Employee Engagement in Increasing Talent Retention at A Crude Palm Oil Company - Amelia, Dea; Sukmawati, Anggraini; Syafitri, Utami Dyah (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This study examines the effect of employee engagement on talent retention at PT. Wilmar Nabati Indonesia, Dumai, with reward system as a mediating variable. Data were collected from 177 employees through an online questionnaire and analyzed using SEM-PLS with SmartPLS 3.0. Respondents were classified by age, tenure, and educational background. The results show that employee engagement has a positive and significant effect on talent retention. Furthermore, reward system mediates the relationship between employee engagement and talent retention. These findings emphasize the importance of fostering employee engagement and developing effective reward systems to retain critical talent in the crude palm oil industry. The study contributes to the literature by positioning reward system as a mediator, a perspective that has received limited attention in previous research. HR managers should focus on appreciation and clear promotion paths to improve retention.